2014
DOI: 10.4049/jimmunol.1302448
|View full text |Cite
|
Sign up to set email alerts
|

TLR3–Responsive, XCR1+, CD141(BDCA-3)+/CD8α+-Equivalent Dendritic Cells Uncovered in Healthy and Simian Immunodeficiency Virus–Infected Rhesus Macaques

Abstract: In mice, CD8α+ myeloid dendritic cells (mDC) optimally cross-present Ags to CD8+ T cells and respond strongly to TLR3 ligands. Although equivalent DC have been identified by comparative genomic analysis and functional studies in humans as XCR1+CD141 (BDCA-3)+Clec9A+cell adhesion molecule 1+ mDC, and in sheep as CD26+ mDC, these cells remained elusive in nonhuman primates. To remedy this situation, we delineated precisely DC and monocyte populations by 12-color flow cytometry and transcriptomic analyses in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 68 publications
(108 reference statements)
2
41
0
Order By: Relevance
“…XCR1 + CD34-DC expressed the molecular signature characteristic of XCR1 + bDC, including the chemokine receptor XCR1, which likely promotes physical interactions with CD8 + T cells (8,13), the endocytic receptor CLEC9A, which promotes crosspresentation of Ag derived from dying cells (43), the adhesion receptor CADM1, which may promote the induction of CTL responses (44), and the pattern recognition receptor TLR3, which allows sensing of dsRNA including responsiveness to the synthetic adjuvant PolyI:C. CD1c and CD141 are not reliable markers of human DC subsets, because they were expressed on all the three in vitro-derived DC subsets studied in this work, consistent with similar observations reported for ex vivo-isolated human DC subsets (7,11,42). Hence, flow cytometry assessment of cell surface expression of the discriminative markers XCR1 or CLEC9A and CADM1, or gene expression profiling, are critical to ensure the identity of HLA-DR + CD141 + cells in humans (7,8,11,36).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…XCR1 + CD34-DC expressed the molecular signature characteristic of XCR1 + bDC, including the chemokine receptor XCR1, which likely promotes physical interactions with CD8 + T cells (8,13), the endocytic receptor CLEC9A, which promotes crosspresentation of Ag derived from dying cells (43), the adhesion receptor CADM1, which may promote the induction of CTL responses (44), and the pattern recognition receptor TLR3, which allows sensing of dsRNA including responsiveness to the synthetic adjuvant PolyI:C. CD1c and CD141 are not reliable markers of human DC subsets, because they were expressed on all the three in vitro-derived DC subsets studied in this work, consistent with similar observations reported for ex vivo-isolated human DC subsets (7,11,42). Hence, flow cytometry assessment of cell surface expression of the discriminative markers XCR1 or CLEC9A and CADM1, or gene expression profiling, are critical to ensure the identity of HLA-DR + CD141 + cells in humans (7,8,11,36).…”
Section: Discussionsupporting
confidence: 74%
“…Human XCR1 was stained with a fluorescently coupled recombinant human chemokine ligand vaccibody (rhXCL1-mCherry) (36). FS36 and FS3T cultures were sorted into .97% pure DC subsets with a FACSAria cytometer (BD Biosciences), based on viability (negativity for Sytox blue; Invitrogen) and expression of CD141 and CD11c.…”
Section: In Vitro Generation Of Xcr1mentioning
confidence: 99%
“…In pig and macaques, cDC1 were the only cells to strongly express CADM1. In macaques, cDC1 were also XCR1 positive and expressed CLEC9A and BATF3 at the RNA level; similar to human cDC1, they also strongly expressed CD205 and CD162 and were responsive to TLR3 triggering [75,76]. cDC that closely resemble cDC1 in terms of FLT3, CADM1, CD205, TLR3 and XCR1 expression, were also identified for the first time in a non-mammalian species, the chicken [77].…”
Section: Xcr1 + Cadm1 + Cdc1 Across Speciesmentioning
confidence: 77%
“…These recent studies confirmed that BATF3, XCR1, CADM1, TLR3 and, to a lesser extent, CLEC9A are conserved markers of cDC1 across species. CLEC9A was detected only at the RNA level both in macaque [75] and sheep [77], but surface protein expression was only detectable on CADM1 + XCR1 + cDC1 in 2 of the 27 macaques tested [75]. Among leukocytes, cDC1 also have the highest expression level of other molecules including CD205 (DEC-205) in mouse, human, macaque and sheep [61,75,78], CD162 in human and macaque [51,75], and CD26 in mouse, human and sheep [46,61,79].…”
Section: Xcr1 + Cadm1 + Cdc1 Across Speciesmentioning
confidence: 82%
See 1 more Smart Citation